Perubahan sosial di Yogyakarta Selo Sumarjan ; penerjemah, Mochtar Pabotinggi ; penyunting, Fadly Kurniawan. - SELO SUMARJAN; Fadly Kurniawan; Mochtar Pabotinggi (2009)
xxxvi, 508 hlm. ilus. 21 cm (2 eks.)